2008
DOI: 10.1002/elps.200700780
|View full text |Cite
|
Sign up to set email alerts
|

System peaks in micellar electrophoresis: I. Utilization of system peaks for determination of critical micelle concentration

Abstract: A new way to determine the critical micelle concentration (CMC) based on the mobilities of system peaks is presented. A general approach for the CMC determination is based on the change of the slope or on finding the inflection point in the plot of a physical property of solution as a function of surfactant concentration. The determination of CMC by system peaks in CE utilizes a "jump" instead of a continuous change in the measured quantity. This phenomenon was predicted by the program PeakMaster, which was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The CMC values were determined from the fraction of complexed dye and they are listed in Table . The CMC values are higher than in buffered solution as already shown in literature , however, we were able to observe the same trends in micelle formation and we were able to determine CMC up to 30% ACN. It has to be pointed out that the CMC value in ACN‐free solution is slightly lower than generally accepted value 8.4 mM, which is most probably caused by electrostatic interaction of the positively charged rhodamine with SDS molecules.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The CMC values were determined from the fraction of complexed dye and they are listed in Table . The CMC values are higher than in buffered solution as already shown in literature , however, we were able to observe the same trends in micelle formation and we were able to determine CMC up to 30% ACN. It has to be pointed out that the CMC value in ACN‐free solution is slightly lower than generally accepted value 8.4 mM, which is most probably caused by electrostatic interaction of the positively charged rhodamine with SDS molecules.…”
Section: Resultssupporting
confidence: 88%
“…Lokajová et al. showed that the mobility of system peaks can change by prompt “jump,” when the CMC is reached and micelles are formed. This allows determining the CMC with very high precision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other methods have been developed for CMC determinations. Non-invasive physical methods include capillary electrophoresis [81][82][83], speed of sound measurements [84,85], resonance Rayleigh scattering [86], static and dynamic light scattering [74,87,88], potentiometry [89], nuclear magnetic resonance, NMR [90,91], diffusion ordered spectroscopy NMR [92,93], ultrasonic spectroscopy [94], fiber-optical measurements [95], induction current [96], chemiluminescence [97] and chiroptical spectroscopic methods [98].…”
Section: Scientific Challenges 51 Surfactantsmentioning
confidence: 99%
“…This software was chosen due to its easiness and because it has been extensively validated with numerous experimental works [8,19,20].…”
Section: Instrumentmentioning
confidence: 99%